Estudio de prefactibilidad para la creación de una Empresa procesadora de papa Criolla precocida (2023)
This project presented shows the development that was carried out to perform a business idea for a company that will be dedicated to the processing about criolla potato pre-cooked in the status of freezing, in the search of generate a business opportunity and that it could be a support to the local economy, in this case on the city Duitama, on the development about the study of pre-feasibility were focused the efforts in the way to search alternatives that could give project viability that counts on an investigative line based on productivity, competitively and innovation. To the project realization were determined a market study with the point to get clarity about the actual status on the region market, a technical analyze to determine factors as the location, plant design and finally were realized a financial study determined to the viability according to the expenses and inversions that needs to make to the materialize the project.